Pemanfaatan Kulit Ikan Lele Sebagai Bahan Baku Keripik Ikan - Nikmawatisusanti Yusuf; Asri Silvana Naiu; Sri Rahayu Kalaka (LPPM Uncen, 2025)
Catfish is one of the most widely cultivated freshwater fish and serves as an important source of animal protein. Beyond its flesh, catfish skin possesses potential as a raw material for developing nutritious and economically valuable food products such as fish-skin chips. This community service activity involved counseling and hands-on training for local catfish farmers and households. The program introduced techniques for processing catfish skin into chips, focusing on practical demonstrations and participatory learning. The activity revealed a strong interest and willingness among participants, particularly catfish farmers, housewives, and young women, to utilize catfish skin as a processed product. Participants actively engaged in the training sessions. The resulting product was catfish-skin chips with favorable characteristics, including crispiness, savory taste, and preferred seasoning and aroma. The activity successfully enhanced community knowledge, skills, and motivation in diversifying fish-based products. By introducing catfish-skin chips as a value-added product, the program demonstrated an effective way to transform aquaculture by-products into healthy, nutritious, and economically beneficial foods.